(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The requirement for public tenders in public administration arises as a rule that aims to ensure the pillars of an isonomic state with a collective face, in which the principle of the unavailability of the public interest is in force. In this context, when it comes to direct contracting, it must be recognized that the core of the main discussions on the subject revolves around the possible violation of principles that legitimize the state. Addressing this issue is the aim of this article. To this end, using a qualitative methodological approach, a descriptive and explanatory study will be carried out, through an analysis of the new legislation and a bibliographical survey, with the aim of examining how direct contracting within the scope of public administration can effectively refer to a need to meet a concretely identified public interest. To this end, the provisions of the new Bidding Law (Law 14.133/2021) will be analyzed, referring to the procedure for direct contracting, in the form of unenforceability and waiver of bidding. The hypotheses and requirements of each modality will be highlighted. Finally, considering that this method of contracting presents a set of risks of abuse and violations of the rules and principles that guide the actions of the democratic state, it will be emphasized how the public manager must be more than careful, always attentive to all the requirements that configure and legitimize these forms of contracting, so as not to incur damage to the public interest.